Assessment of parents' awareness with the child education planner and its needs / Noryanty Shamsudin - Shamsudin, Noryanty (Faculty of Business and Management, 2003)
Children's Insurance was inspired because child was precious. Therefore, MCIS Child Education Planner is an ideal solution to ensure that funds is available to meet the child's education expenses and suitable for the parents that find that it is difficult to fulfill this responsibility unless they systematically set aside funds to meet the high and escalating cost of higher education. The Child Education Plan is a unique policy. This policy does not only enable the parent or guardian to systematically accumulate funds to meet the child's higher education needs in the future but also ensures that funds will be available even in the unfortunate event of the parent not being around. Therefore, the objectives of this research study are to determine the level of parents' awareness regarding the existing Child Education Planner introduced by MCIS, to identify the importance of the C.E.P in order to fulfill child future need. And to identify factor (s) that could increase parent awareness and understanding regarding the Child Plan. The study focuses only to the Fazil Agency (MCIS ZURICH Insurance Agent) in the area of Malacca town area using the descriptive research. The collection of the primary data is sourced from questionnaires taken from simple random sampling.